Comparative Characteristics of Martensite and Bainite in Cu-Based SMAs - Elena MIHALACHE; Monica-Nicoleta LOHAN; Bogdan PRICOP; Leandru-Gheorghe BUJOREANU; Marius-Gabriel SURU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2014)
The present work reports the evolution of micro-structure and shape memory behavior in a Cu-15 Zn-6 Al (mass. %) shape memory alloy (SMA), as a function of the applied hot working procedure and of the performed heat treatments. To this purpose a special compressed-air forging hammer was employed. The samples were heated up to 1023 K into an electric furnace and swaged on a compressed-air forging hammer, by multiple blows. After several blows, the specimens were prepared, by maintaining the main plastic deformation direction, for structural analysis, being cut, embedded, ground, polished and etched. Structural analysis comprised optical (OM) and scanning electron (SEM) microscopy observations, performed with the view of emphasizing the morphological aspects of martensite and bainite. To reveal the atomic fluctuations, enabled by hot forging, energy dispersive X-ray spectroscopy analysis (EDS) measurements were performed by means of SEM analysis. The paper reports the results of OM, SEM and EDS observations, by corroborating the results obtained in martensite and bainite.